PROTECTION OF STATE AS AN EXAMPLE OF ETHNIC PATRI-OTISM: THE CASE OF THE JEWS OF AUSTRIAN GALICIA - Монолатій, І. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article analyzes the peculiarities of military service of the Jews o f Galicia late XVIII – early XX centuries, in particular their participation in the protection of the Habsburg monarchy from external enemies. Substantiates the argument that patriotism in relation to non-Jewish state was a major duty of the Jews. Identified a number of methods to attract Jews to military service: the mercy of the army, exemption from military service, equalizing their rights with the other “comrades in arms”, the possibility of officer ranks and perform the ritual prescriptions of Judaism. The nature and motives of pacifist sentiment that dominated among the Jews of Galicia, as well as their mechanisms of evasion of military service.